2016
DOI: 10.1371/journal.pone.0162450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxic Pressure along the Sava River

Abstract: In this study we have performed a comprehensive genotoxicological survey along the 900 rkm of the Sava River. In total, 12 sites were chosen in compliance with the goals of GLOBAQUA project dealing with the effects of multiple stressors on biodiversity and functioning of aquatic ecosystems. The genotoxic potential was assessed using a complex battery of bioassays performed in prokaryotes and aquatic eukaryotes (freshwater fish). Battery comprised evaluation of mutagenicity by SOS/umuC test in Salmonella typhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 52 publications
2
0
0
1
Order By: Relevance
“…6 PCA graph and grouping of analysed fish specimens using as input variables: genotoxicity parameters (TI% in blood, liver and gills), element concentration (B, Ca, Cr, Cu, Fe, K, Mg, Mn, Mo, Se, Sr, Zn) in muscle (M) and liver (L), histopathological index of gills (IG) and liver (IL) and abundance of immature, intermediary and mature erythrocytes high frequencies of MN only in top predator fish. Our findings are consistent with previous research that showed higher sensitivity of comet assay in comparison to MN to estimate the genotoxic potential and discriminate fine differences in the response of ecologically similar species (De Andrade et al 2004;Grisolia et al 2009;Kolarević et al 2016).…”
Section: Histopathological Alterationsupporting
confidence: 93%
“…6 PCA graph and grouping of analysed fish specimens using as input variables: genotoxicity parameters (TI% in blood, liver and gills), element concentration (B, Ca, Cr, Cu, Fe, K, Mg, Mn, Mo, Se, Sr, Zn) in muscle (M) and liver (L), histopathological index of gills (IG) and liver (IL) and abundance of immature, intermediary and mature erythrocytes high frequencies of MN only in top predator fish. Our findings are consistent with previous research that showed higher sensitivity of comet assay in comparison to MN to estimate the genotoxic potential and discriminate fine differences in the response of ecologically similar species (De Andrade et al 2004;Grisolia et al 2009;Kolarević et al 2016).…”
Section: Histopathological Alterationsupporting
confidence: 93%
“…Overall, the results obtained with genotoxicity assays showed that the Comet assay can be a useful tool in biomonitoring of surface waters applying several experimental models in agreement with literature data (Guidi et al, 2017;Kolarevic et al, 2016a;Kolarević et al, 2016b;Deutschmann et al, 2016;Pellegri et al, 2020).…”
Section: Tablesupporting
confidence: 83%
“…Nas últimas décadas, a industrialização e as diversas influências antropogênicas resultaram em uma maior presença de contaminantes em ecossistemas aquáticos (Sunjog et al, 2013). Isso ocorre pois o que é descartado contêm mistura de contaminantes orgânicos e inorgânicos, o que pode acarretar múltiplos efeitos biológicos, induzir alterações genéticas e influenciar a integridade de moléculas de DNA em organismos aquáticos, isso se dá pela interação com múltiplas sequências alvo nos organismos expostos (Kolarevic et al, 2017& Thellmann et al, 2017. Uma das formas de identificar a presença de agentes genotóxicos é o teste do micronúcleo, uma técnica simples que oferece rápido resultado (Bueno et al, 2017).…”
Section: Introductionunclassified